Text and Time: A Theory of Testamentary Obsolescence - Adam J. Hirsch (Washington University Law Review, 2009)
Events may occur after a will is executed that ordinarily give rise to changes of intent regarding the estate plan — yet the testator may take no action to revoke or amend the original will. Should such a will be given literal effect? When, if ever, should lawmakers intervene to update a will on the testator's behalf? This is the problem of testamentary obsolescence. It reflects a fundamental, structural problem in law that can also crop up with regard to constitutions, statutes, and other performative texts, any one of which may become timeworn. This Article develops a theoretical framework for determining when lawmakers should — and should not — step in to revise wills that testators have left unaltered and endeavors to locate this framework in the context of other forms of textual obsolescence. The Article focuses on a variable denoted “friction” — that is, the extent of difficulty text makers face in revising texts on their own. Some testators become incapable of amending their wills, and some events display the dual property of altering testamentary intent while simultaneously disabling the testator from executing a new estate plan. In such instances, legal intervention to effectuate intent is warranted. Where testators remain at liberty to amend their wills following a change of circumstance, however, the case for legal intervention becomes uneasy. Nevertheless, lesser forms of friction may continue to operate, affording testators less practical opportunity to redo their wills, and hence again giving cause for lawmakers to interpret wills dynamically. When they do act to reinterpret a will in light of changed circumstances, lawmakers should ordinarily follow the course that a majority of testators would choose, as default rule theory dictates. Yet, legal intervention to effectuate probable intent could implicate error costs, if testators believe a different rule is in effect. By matching default rules of will interpretation with common assumptions about what rules apply, lawmakers minimize error costs. As this Article demonstrates in the Appendix, under certain conditions an error-minimizing default is more efficient than a majoritarian default, a contribution to default rule theory.
Keywords: Wills; Testamentary capacity; Probate law & practice; Inheritance & succession; Obsolescence